The Deterministic Positivist Epistemological Approach: An Investigation of the Strategies Used by Banking Executives to Improve Employee Retention - ElAlam, Younes; Belkasseh, Mohammed (Archives of Business Research, 2023)
Theory-practice gap speculations are not the only focus of design research. Significant questions about the role of the character of research are also raised by research design. Despite the limitations of this work, it is nonetheless helpful to have a high-level understanding of the key characteristics shared by the three epistemological approaches: the subjectivist, constructivist, and objectivist schools of thought. Considering the existing literature in the topic, these primary epistemological stances that have influenced theories of research design are discussed and analyzed. The purpose of this paper is not to provide a definitive answer based on statistical analysis, but rather to delve into the nuances of the topic at hand. At the end of the paper, we discuss and argue why and how we chose a deterministic positivist epistemological approach to investigate the strategies used by banking executives to improve employee retention: First, we will illustrate that the topic under study does not fit within the constructivist interpretative framework. Then, we will develop key ideas from the research that will form the backbone of the positivist model. We conclude by outlining our plan for an empiricist verification technique and defending its inception from a positivist perspective.